21-year-old silicone breast implants causing recurrent pneumonia, chest pain and coughing. (2020) - Johansen, Nina Järvelä; Hilberg, Ole; Løkke, Anders
Abstract: A 50-year-old former smoker presented with recurrent pneumonia, fever and atypical chest pain on and off for a year and was treated with antibiotics several times. Meanwhile, her lung function deteriorated with an obstructive pattern and therefore she was treated with inhalation medication without effect. Tests of the heart, bronchoscopy, gastroscopy and a CT-scan of the lungs did not reveal the cause. Finally, an FDG-PET scan showed inflammation of the tissue on the backside of a 21-year-old silicone chest implant, which was intact but encapsulated. The chest implants were removed after which the patient has remained free of infections. However, the lung function impairment did not improve, and a new HRCT-scan demonstrated widespread emphysema.